Estudo sobre o efeito de variáveis macro econômico e do spread de credit default swap no risco de evento de crédito soberano - Botelho, Rodrigo Azevedo de Castro (2012)
This paper explores the sovereign default due to the structure of Credit Default Swap spreads. These spreads show the default probability of a country. The methodology proposed in this paper applied for Argentina, Korea, Ecuador, Indonesia, Mexico, Peru, Turkey, Ukraine, Venezuela and Rússia. We could show that a single factor model following a lognormal process captures the probability of default. We also show that the macro economic variables like inflation, unemployment e growth do not explain the dependent variable of this study. Each country responds differently to the economic crisis that leads to don’t honor their commitments debts.